What motivates WA public to give money to not-for-profit organisations - Oroz, I.; Shanka, Tekle; Handley, Brian (School of Marketing, Curtin Business School, 2008)
This study presents the results of an exploratory investigation of the giving behaviour among Western Australians (WA) using an established scale (Sargeant, Ford and West, 2006) to ensure comparability with earlier research. A convenience sample of 400 members of the general public in WA voluntarily participated in a survey to explore motivations behind giving money to charities and non-profit organisations. The survey results provide important new insights into giving patterns in WA. Trust has been highlighted as a significant motivational factor in the commitment to continue to give. The level of commitment is also linked to the performance of the organisation and its ability to communicate with its stakeholders. Results also indicate a positive causal link between the degree of commitment and intention to give in the future. Results are discussed and further research directions are suggested.